2013
DOI: 10.5296/jfs.v2i1.3747
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Altitude Variation on Trigonelline Content during Ontogeny of Coffea Canephora Fruit

Abstract: Trigonelline is a nicotinic acid related alkaloid abundant in coffee beans. The influence of altitude variations on trigonelline and its precursor nicotinic acid content of beans of Robusta coffee plants that collected from different elevations were investigated. Both nicotinic acid and trigonelline contents were always higher at all stages of coffee fruit ontogeny from plants grown at higher elevations. Maximum nicotinic acid and trigonelline content of 5.164 ± 0.131 mg and 975.8 ± 7.24 mg/100 g Fresh weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
4
0
2
Order By: Relevance
“…Hasil penelitian pada kopi Arabika varietas Bourbon menunjukkan bahwa semakin tinggi tempat tumbuh, akan semakin meningkat kandungan trigonelline (Barbosa et al, 2012;Bertrand et al, 2012;Figueiredo et al, 2013). Hal yang sama terjadi juga pada jenis Robusta (Sridevi & Giridhar, 2013). Trigonelline merupakan salah satu alkaloid yang banyak menimbulkan senyawa flavor pada kopi, seperti alkil-pyradines dan pyrroles (De Maria, Trugo, Moreira & Werneck 1994 cited in Sridevi & Giridhar, 2013).…”
Section: B Pengaruh Ketinggian Tempatunclassified
See 1 more Smart Citation
“…Hasil penelitian pada kopi Arabika varietas Bourbon menunjukkan bahwa semakin tinggi tempat tumbuh, akan semakin meningkat kandungan trigonelline (Barbosa et al, 2012;Bertrand et al, 2012;Figueiredo et al, 2013). Hal yang sama terjadi juga pada jenis Robusta (Sridevi & Giridhar, 2013). Trigonelline merupakan salah satu alkaloid yang banyak menimbulkan senyawa flavor pada kopi, seperti alkil-pyradines dan pyrroles (De Maria, Trugo, Moreira & Werneck 1994 cited in Sridevi & Giridhar, 2013).…”
Section: B Pengaruh Ketinggian Tempatunclassified
“…Hal yang sama terjadi juga pada jenis Robusta (Sridevi & Giridhar, 2013). Trigonelline merupakan salah satu alkaloid yang banyak menimbulkan senyawa flavor pada kopi, seperti alkil-pyradines dan pyrroles (De Maria, Trugo, Moreira & Werneck 1994 cited in Sridevi & Giridhar, 2013). Hasil penelitian lain pada kopi Arabika juga menunjukkan adanya peningkatan kandungan glukosa dan atribut flavor sejalan dengan semakin tingginya tempat tumbuh (Joët et al, 2010).…”
Section: B Pengaruh Ketinggian Tempatunclassified
“…No less than 1000 volatile compounds are generated during the roasting process, and between 25 and 35 are responsible for the coffee aroma (Mestdagh et al 2014). Thus, many factors that change from the harvest of green coffee beans to the consumption of a steaming cup of coffee influence the metabolome of this beverage: Coffee plant species (genetic factor) (Kitzberger et al 2014) as well as geographical origin and growing conditions (climate, altitude, light, soil, temperature…) (Wei et al 2012a), diseases and symbiosis (pest and fungi) (Sbrana et al 2014), harvesting (period), fruit development (Sridevi and Parvatam 2013), drying (dry or wet method) (Duarte et al 2010), roasting process (duration, shaking, temperature, sugar addition) (Ludwig et al 2013a;Wei et al 2012b), grinding, storage (duration, conditions) (Belviso et al 2014;Yeretzian et al 2012) and coffee-making and serving techniques (process, time, hot or cold water, additives…) (Afify et al 2011;Andueza et al 2009;Caporaso et al 2014;Durak et al 2014;Ludwig et al 2012;Tagliazucchi et al 2012) are factors known to influence and modulate the chemical composition of a cup of coffee ready for consumption. Finally, after ingestion, the native coffee metabolites are degraded and modified by the gut microbiome and endogenous enzymes during the digestion process to generate new bioactive compounds (Fig.…”
Section: A Pharmacy In Your Cupmentioning
confidence: 99%
“…The differences could be attributed to the differences in extraction methods. It was shown that trigonelline is a bitter alkaloid in coffee which serves to produce important aroma compounds [30]. Trigonelline partially degrades during roasting to produce two important compounds -pyridines and nicotinic acid -such that a very dark roast will have only a fraction of its original trigonelline content.…”
Section: High Performance Liquid Chromatographic Separation and Determentioning
confidence: 99%